Benzenoid Aromatics from Renewable Resources - Zheng, Shasha; Zhang, Zhenlei; He, Songbo; Yang, Huaizhou; Atia, Hanan; Abdel-Mageed, Ali M; Wohlrab, Sebastian; Baráth, Eszter; Tin, Sergey; Heeres, Hero J; Deuss, Peter J; de Vries, Johannes G (Chemical reviews, 2024)
In this Review, all known chemical methods for the conversion of renewable resources into benzenoid aromatics are summarized. The raw materials that were taken into consideration are CO ; lignocellulose and its constituents cellulose, hemicellulose, and lignin; carbohydrates, mostly glucose, fructose, and xylose; chitin; fats and oils; terpenes; and materials that are easily obtained via fermentation, such as biogas, bioethanol, acetone, and many more. There are roughly two directions. One much used method is catalytic fast pyrolysis carried out at high temperatures (between 300 and 700 °C depending on the raw material), which leads to the formation of biochar; gases, such as CO, CO , H , and CH ; and an oil which is a mixture of hydrocarbons, mostly aromatics. The carbon selectivities of this method can be reasonably high when defined small molecules such as methanol or hexane are used but are rather low when highly oxygenated compounds such as lignocellulose are used. The other direction is largely based on the multistep conversion of platform chemicals obtained from lignocellulose, cellulose, or sugars and a limited number of fats and terpenes. Much research has focused on furan compounds such as furfural, 5-hydroxymethylfurfural, and 5-chloromethylfurfural. The conversion of lignocellulose to xylene via 5-chloromethylfurfural and dimethylfuran has led to the construction of two large-scale plants, one of which has been operational since 2023.